2017
DOI: 10.1016/j.biopsych.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Preadolescent Adversity Programs a Disrupted Maternal Stress Reactivity in Humans and Mice

Abstract: Background Adverse childhood experiences (ACEs) are one of the greatest predictors for affective disorders for women. Periods of dynamic hormonal flux, including pregnancy, exacerbate the risk for affective disturbance and promote hypothalamic-pituitary-adrenal (HPA) axis dysregulation, a key feature of affective disorders. Little is understood as to how stress experienced in late childhood, defined as preadolescence, alters the programming unique to this period of brain maturation and its interaction with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 64 publications
2
45
0
1
Order By: Relevance
“…Our previous translational study found that high ACE postpartum women exhibited a blunted cortisol response to acute stress, mirroring hyporesponsive HPA function in postpartum female mice exposed to ELS (Morrison et al, 2017). However, in the present sample there was no main effect of ACE on proinflammatory cytokine response to stress.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our previous translational study found that high ACE postpartum women exhibited a blunted cortisol response to acute stress, mirroring hyporesponsive HPA function in postpartum female mice exposed to ELS (Morrison et al, 2017). However, in the present sample there was no main effect of ACE on proinflammatory cytokine response to stress.…”
Section: Discussionmentioning
confidence: 94%
“…Scores range from 0–10 and reflect the occurrence(s) of event(s), not their frequency or severity. An ACE score >=2 is associated with increased risk of preterm birth (Christiaens et al, 2015) and altered HPA axis function during pregnancy (Bowers et al, 2018) and postpartum (Morrison et al, 2017). Thus, participants scoring 2 or greater were considered “high ACE” while subjects with ACE score of <2 were considered “low ACE.”…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(10) describe the impact that stress in the preadolescent period has on adult HPA regulation. They demonstrate that in both mice and human women, exposure to stress during the preadolescent period leads to dysregulated stress responses that emerged only during pregnancy and the peripartum period, suggesting that these long-lasting behavioral and endocrine effects emerge only within the hormonal milieu of pregnancy.…”
mentioning
confidence: 99%